2005
DOI: 10.1142/s0217979205030323
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of Micron by Nanometer Scale Powders in Magnetorheological Fluids

Abstract: The effects of substitution of micron size powder by nanometer size powder in magnetorheological (MR) fluids are investigated in this study. Three MR fluid samples containing iron powder with 45% weight fraction in a carrier fluid were made by Materials Modification Inc. The difference among these three fluids is size of the magnetic particles. The first MR fluid sample contained only micron size iron powder with lO^m particle size. In the second sample, 5% micron iron was substituted with nano powders having … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…Fe nanoparticle is one of the best candidates for MR fluids due to its high saturation magnetization [1,10], among other magnetic nanoparticles such as ferrites [3,[6][7][8] and alloys [9]. Fe nanoparticles for MR fluids have been synthesized using a microwave plasma technique, with an average diameter of 20 nm [10] and 28 nm [11,12]. Although MR fluids containing Fe nanoparticles increased the stability against sedimentation, the yield stress obtained for the same magnetic field level was drastically reduced in comparison to fluids containing micron-sized Fe particles.…”
Section: Introductionmentioning
confidence: 99%
“…Fe nanoparticle is one of the best candidates for MR fluids due to its high saturation magnetization [1,10], among other magnetic nanoparticles such as ferrites [3,[6][7][8] and alloys [9]. Fe nanoparticles for MR fluids have been synthesized using a microwave plasma technique, with an average diameter of 20 nm [10] and 28 nm [11,12]. Although MR fluids containing Fe nanoparticles increased the stability against sedimentation, the yield stress obtained for the same magnetic field level was drastically reduced in comparison to fluids containing micron-sized Fe particles.…”
Section: Introductionmentioning
confidence: 99%
“…The flow index (n) constantly maintains a value less than unity, which indicates that the post-yield flow is nonlinear and shear thinning. It is notable that unlike the constant flow index characteristic of nanocobalt-based MR fluids (Chaudhuri et al, 2005), the flow index for nanoiron-based MR fluids decreases steadily with increasing magnetization. Figure 6 shows plots of the experimental data with the superimposed BP and HB models.…”
Section: Resultsmentioning
confidence: 86%
“…Nanometer-sized iron particles, ranging from 10 to 100 nm, were introduced to reduce settling while maintaining useful yield stress levels (Kormann et al, 1992;Taketomi et al, 1993;Rosenfeld et al, 2002). It was shown that the introduction of nanoparticles reduced settling (John et al, 2002;Trihan et al, 2003), but the yield stresses for MR fluids having constant solids loading was reduced when nanoparticles were substituted for micron scale particles in the MR suspension (Poddar et al, 2004;Chaudhuri et al, 2005). However, the shear stresses in these fluids are comparable with shear stresses achieved in conventional electrorheological (ER) fluids and the phenomenon is also seen to be temperature dependent.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, long-term settling stability is a major problem caused by the high density and large size of the magnetic particles used. A range of surfactants and additives have been applied to improve dispersion stability of the MR fluids [9][10][11]. Encapsulating magnetic particles with low density materials is another way of improving the settling stability of MR fluids.…”
Section: Introductionmentioning
confidence: 99%